A kukoricapiac és a bioetanol termelés hazai persektívái - Czagány, László (Jelenkori Társadalmi és Gazdasági Folyamatok, 2007)
The EU's grain intervention system brought the Hungarian corn producers into a favorable situation. In the last years record breaking quantities of corn were produced, and a large part of it was offered for intervention procurement. More than 90% of the Union's intervention corn stocks are in Hungary. The European Commission decided on a gradual abolishment of the corn intervention. Hungarian corn producers, however, will not see a decline in their market position, because volume of ethanol fuel production is expected to rise in the coming years, with a substantial demand for raw material. Experts think, that Hungarian development plans are exaggerated, because they are not validated by either corn production capacity, or prospective demand for ethanol fuel.